Stereotactic Body Radiotherapy (SBRT) for Oligometastatic Lung Nodules: A Single Institution Series - Wegner, Rodney E.; Abel, Stephen; Hasan, Shaakir; Schumacher, Lana Y.; Colonias, Athanasios (Frontiers in Oncology, 2019)
Abstract: Aim: Lung metastases from an extra-pulmonary origin occasionally present with a limited metastatic disease burden. In cases where metastatectomy is not feasible, stereotactic body radiation therapy (SBRT) represents a non-invasive, efficacious option. We report the outcomes of patients treated with lung SBRT in cases of limited metastatic disease. Methods: We retrospectively reviewed outcomes in 44 patients with 50 lung nodules from various extra-pulmonary malignancies treated with SBRT. Fifty percent of the patients were male and median age was 64. The median number of nodules was 1 and 90% of patients had oligometastatic disease. Thirty-four percent of patients had extra-thoracic disease. Results: Fifty lung nodules were treated with SBRT in 44 patients. Median dose was 48 Gy in 5 fractions with a median biological effective dose (BED) of 100 Gy10. Follow-up imaging was available for review in 96% of nodules. Median follow-up was 17.5 months. One year local control was 82%. BED >72 Gy10 predicted improved local control (90% vs 57% at 1 year). One year overall survival following SBRT was 66%. There was no difference in overall survival if patients had extra-thoracic disease. Conclusion: Lung SBRT is a safe, effective tool for treatment of limited lung metastases. Dose selection remains important for local control.